2016
DOI: 10.1007/s10827-016-0615-7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between synaptic inhibition and glial-potassium dynamics leads to diverse seizure transition modes in biophysical models of human focal seizures

Abstract: How focal seizures initiate and evolve in human neocortex remains a fundamental problem in neuroscience. Here, we use biophysical neuronal network models of neocortical patches to study how the interaction between inhibition and extracellular potassium ([K+]o) dynamics may contribute to different types of focal seizures. Three main types of propagated focal seizures observed in recent intracortical microelectrode recordings in humans were modelled: seizures characterized by sustained (∼30−60 Hz) gamma local fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
(119 reference statements)
1
13
0
Order By: Relevance
“…This mechanism remains valid for other nonlinear functions such as sigmoidal firing-rate functions. Although LVFA oscillations have been associated with inhibitory activity at seizure onset 28 , 34 and are consistent with the inhibitory veto hypothesis 17 , 35 , our model points to a more general dynamical mechanism for how LVFA oscillations can effectively hinder seizure propagation. The dynamical mechanism is more general in the sense that other sources of LVFA oscillations, not necessarily requiring the intervention of surround inhibition (inhibitory veto), can lead to the same hampering effect.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This mechanism remains valid for other nonlinear functions such as sigmoidal firing-rate functions. Although LVFA oscillations have been associated with inhibitory activity at seizure onset 28 , 34 and are consistent with the inhibitory veto hypothesis 17 , 35 , our model points to a more general dynamical mechanism for how LVFA oscillations can effectively hinder seizure propagation. The dynamical mechanism is more general in the sense that other sources of LVFA oscillations, not necessarily requiring the intervention of surround inhibition (inhibitory veto), can lead to the same hampering effect.…”
Section: Resultssupporting
confidence: 80%
“…The slow variable v ( t ) is termed the “permittivity” variable, as it represents the distance of the Epileptor state to the seizure threshold, i.e., the ability of the model to resist to seizure triggering events. The slow permittivity variable captures slowly evolving physiological processes in the brain, such as changes in the extracellular concentration of different ions 24 28 , metabolism 29 , 30 , and tissue oxygenation 31 , 32 . The Epileptor’s ability to transition into seizures autonomously is mediated by an excitability parameter ( u 0 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) We included a model of depolarization block, so that the firing rate of each population approaches zero as the voltage exceeds −20 mV; that is, we apply a Gaussian activation function, rather than the standard sigmoid function78. Some recent observations from human seizing cortex suggest an important role for depolarization block7879, while others suggest this role may depend on the type of seizure2380. We do not find a critical role for depolarization block in the large amplitude, low-frequency dynamics simulated here.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we found that high frequency firing in GABAergic interneurons could cause the exhaustion of the presynaptic neurotransmitter GABA in a low Mg 2+ /high K + seizure model, therefore leading to the transition of network activity to seizure [ 57 ]. Computer simulation predicted that certain focal seizures could be triggered by GABA depletion [ 59 ]. It remains to be seen if depletion of presynaptic GABA is presented in in vivo animal models of seizure.…”
Section: Introductionmentioning
confidence: 99%